Mapping the organizational socialization and onboarding literature: a bibliometric analysis of the field - Eva Didion; Maria Rosario Perello-Marin; Daniel Catala-Perez; Ute Ambrosius (Cogent Business & Management, 2024)
This study provides a comprehensive review of the intellectual structure and current dynamics of onboarding and socialization research. Using the Web of Science (WoS) database, we found 452 research articles that met the inclusion criteria. Biblioshiny R-package and VOSviewer were used for the bibliometric analysis. We lay out the most prolific authors, journals, institutions and articles in this rapidly growing field. We find that current research is scattered all over different topics and disciplines. We identify five research fronts that authors have pursued in the last 5 years. Researchers have focused on: psychological contracts; the role of networks and relationship building; the changing work contexts in which organizational socialization takes place; the effects of newcomer proactivity and interactions with supervisors; onboarding in distinct areas like software engineering. Promising research avenues in this field can be distinguished in: different groups of newcomers; examining interactive effects between newcomers and socialization agents; and analyzing the evolving area of digital and virtual onboarding and organizational socialization.Efficient onboarding practices and processes not only expedite the productivity of new hires but also increase retention, satisfaction, and engagement. Using bibliometric methods, we analyze 452 research articles, unveiling key contributors and pivotal works in the evolving field of onboarding and organizational socialization. We carve out five research areas that hold potential for future research endeavors. By offering insights into the dynamics of successful organizational socialization, our work holds profound implications for cultivating welcoming and efficient workplaces for managers and HR departments.
Keywords: 650; Bibliometric analysis; onboarding; organizational socialization; newcomer; adjustment